Sex and age differences in sST2 in cardiovascular disease - Beetler, Danielle J.; Bruno, Katelyn A.; Di Florio, Damian N.; Douglass, Erika J.; Shrestha, Swikriti; Tschöpe, Carsten; Cunningham, Madeleine W.; Krejčí, Jan; Bienertová-Vašků, Julie; Pankuweit, Sabine; McNamara, Dennis M.; Jeon, Eun-Seok; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims The goal of this study was to determine whether sex and age differences exist for soluble ST2 (sST2) for several cardiovascular diseases (CVDs). Methods We examined sST2 levels using an ELISA kit for myocarditis (n = 303), cardiomyopathy (n = 293), coronary artery disease (CAD) (n = 239), myocardial infarct (MI) (n = 159), and congestive heart failure (CHF) (n = 286) and compared them to controls that did not have CVDs (n = 234). Results Myocarditis occurred in this study in relatively young patients around age 40 while the other CVDs occurred more often in older individuals around age 60. We observed a sex difference in sST2 by age only in myocarditis patients (men aged 38, women 46, p = 0.0002), but not for other CVDs. Sera sST2 levels were significantly elevated compared to age-matched controls for all CVDs: myocarditis (p ≤ 0.0001), cardiomyopathy (p = 0.0009), CAD (p = 0.03), MI (p = 0.034), and CHF (p < 0.0001) driven by elevated sST2 levels in females for all CVDs except myocarditis, which was elevated in both females (p = 0.002) and males (p ≤ 0.0001). Sex differences in sST2 levels were found for myocarditis and cardiomyopathy but no other CVDs and were higher in males (myocarditis p = 0.0035; cardiomyopathy p = 0.0047). sST2 levels were higher in women with myocarditis over 50 years of age compared to men (p = 0.0004) or women under 50 years of age (p = 0.015). In cardiomyopathy and MI patients, men over 50 had significantly higher levels of sST2 than women (p = 0.012 and p = 0.043, respectively) but sex and age differences were not detected in other CVDs. However, women with cardiomyopathy that experienced early menopause had higher sST2 levels than those who underwent menopause at a natural age range (p = 0.02). Conclusion We found that sex and age differences in sera sST2 exist for myocarditis, cardiomyopathy, and MI, but were not observed in other CVDs including CAD and CHF. These initial findings in patients with self-reported CVDs indicate that more research is needed into sex and age differences in sST2 levels in individual CVDs.